2020
DOI: 10.1166/jbn.2020.2936
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Treatment of Atherosclerosis by Dexamethasone Acetate and Rapamycin Co-Loaded mPEG-DSPE Calcium Phosphate Nanoparticles

Abstract: Atherosclerosis (AS) is one of the leading causes of vascular disease, producing high morbidity and mortality in many countries. Autophagy plays an important role when cells are facing serious circumstances, such as oxidative stress induced by Ox-LDL (oxidized low-density lipoprotein). Recent studies have revealed that DEX (dexamethasone acetate) and RAPA (rapamycin) exhibit efficient AS therapeutic ability by protecting endothelial cells and killing foam cells, respectively. Herein, we hypothesize that combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 16 DR-NPs (DEX and RAPA-coloaded mPEG2k-DSPE calcium phosphate nanoparticles) efficiently aggregated at atherosclerosis plaques in the abdominal artery in mice and exhibited excellent plaque regression ability by inducing autophagy, with smaller necrotic cores and lipid core areas observed after in vivo treatment. 17 Mechanistically, miR-100 indirectly stimulated endothelial autophagy in vitro and in vivo, and attenuated aortic atherogenesis, resulting in a decrease of plaque area by 45%. 18 The occurrence process of carotid atherosclerosis includes four pathological stages: intimal thickening, intimal xanthoma, thin fiber cap atheroma and thick fiber cap atheroma.…”
Section: Introductionmentioning
confidence: 99%
“… 16 DR-NPs (DEX and RAPA-coloaded mPEG2k-DSPE calcium phosphate nanoparticles) efficiently aggregated at atherosclerosis plaques in the abdominal artery in mice and exhibited excellent plaque regression ability by inducing autophagy, with smaller necrotic cores and lipid core areas observed after in vivo treatment. 17 Mechanistically, miR-100 indirectly stimulated endothelial autophagy in vitro and in vivo, and attenuated aortic atherogenesis, resulting in a decrease of plaque area by 45%. 18 The occurrence process of carotid atherosclerosis includes four pathological stages: intimal thickening, intimal xanthoma, thin fiber cap atheroma and thick fiber cap atheroma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the side effects of PEDF RNPs on kidneys, spleen, liver, lungs, and heart were determined by H&E staining, and liver and kidney function was also assessed. C57 mice of the same age were taken as a negative control …”
Section: Methodsmentioning
confidence: 99%
“…Rapamycin inhibits the proliferation of pulmonary vascular cells, including VSMCs and endothelial cells by inhibiting mTORC1 and mTORC2. 88,[118][119][120][121] Notably, preclinical research data have shown that rapamycin treatment, both acute and chronic, has strong antiproliferation effects and can prevent the development of pulmonary vascular remodeling in rats with pulmonary hypertension. 3,88,122 However, clinical studies have shown that both short-term and long-term rapamycin therapy, while having antiproliferative effects and inhibiting the progression of pulmonary vascular remodeling, still fails to induce apoptosis and reverse pulmonary vascular remodeling in patients with IPAH and normal human PASMCs under chronic hypoxic conditions.…”
Section: Rapamycin and Pahmentioning
confidence: 99%